Optical Spectroscopy for Biofuel Composition Sensing. (2016) - Middelburg, L.M.; de Graaf, G.; Ghaderi, M.; Bossche, A.; Bastemeijer, J.; Visser, J.H.; Soltis, R.E.; Wolffenbuttel, R.F.
Abstract: The optical absorption of water-containing bio-fuel is investigated as a parameter to determine the gasoline content of this fuel. Optical measurements reveal that gasoline shows an interesting and useful spectrum with typical absorption behavior in the UV range between 230 and 300 nm. This result indicates that significant information can be obtained to determine the gasoline concentration in bio-fuel by UV absorption spectroscopy. A concept for a low-cost measurement system in the fuel line is presented, by implementing a LVOF in combination with a wide-band light source and detector arrays.